Some Physical Characteristics and Protein Content of Soybean for Instant Soymilk - Ita Yustina; Nurul Istiqomah; Farid Rakhmat Abadi (agriTECH, 2020)
The increment of soybean consumption demands product diversification. One example of soybean-based product is extracted soybean in the form of soymilk, which has the following weaknesses: short shelf life, unpleasant aroma, and impractical processing. Therefore, it is necessary to investigate the processing of instant soymilk compared with its brewed solutions using hot and cold water. This experiment will use a completely randomized block design with two factors: the soybean variety ( i.e., Kaba, Burangrang, Anjasmoro, and Argomulyo) and the time to oven of 20 and 30 minutes. The soybean's physical characteristics that will be observed include width, length, thickness, volume, and weight per 100 beans, whereas the powder characteristics shall include yield, moisture, protein content, and degree of lightness. In addition, the characteristics of brewed solutions will be measured using an organoleptical test. The results show that the Argomulyo variety has the biggest size among others, and the Anjasmoro variety contains the highest protein content (38.05%), whereas the Kaba variety has the lowest starch content (4.15%). The best instant soybean powder was the Anjasmoro variety with a time to oven of 20 minutes and the highest protein content (7.88%), where the value of lightness L = 83.4; a = 3.40, and b = 17.95. Moreover, the organoleptical test result for powder color scored 4.16, and the unfavorable aroma was 3.37, whereas the solutions' color was 3.74; favorable aroma was 2.16; taste was 2.11; while the overall preference was 2.26.